Construyendo Inseguridades. Aproximaciones a la violencia en Centroamérica desde el análisis del discurso; Constructed insecurities. Discourse analysis and the understanding of violence in Central America - Sebastian Huhn; Anika Oettler; Peter Peetz (German Institute of Global and Area Studies (GIGA), 2006)
In all Central American countries we witness a struggle to define, interpret and classify types of violence, delinquency, crime and (in)security. Although this struggle has highly relevant political and social implications, it has not been analyzed systematically. This article evaluates the state of the art and, based on methodological considerations, emphasizes the contribution of qualitative research on the local level in contrast to quantitative studies on the national or regional level. In a second step, using the discourse on Central American youth gangs as an example, the authors show that moral panic and repressive criminal policies are not direct consequences of the violence phenomena per se. Rather, the perception of and the reactions to insecurity and violence are based on social discourses about these phenomena.
Keywords: 300; Central America; violence; delinquency; insecurity; discourse analysis